Digital Space of Leading Universities: The Comparative Analysis of Sites - E. V. Brodovskaya; A. Yu. Dombrovskaya; T. E. Petrova; R. V. Pyrma; A. A. Azarov (Высшее образование в России)
The article presents the results of a comparative and typological analysis of open data websites of the leading Russian and foreign universities. The analysis has been carried out in order to assess the state of the digital environment of universities in the areas of career guidance of students, the development of students’ competencies and career support of graduates. The authors adduce an empirical evidence of the key problems of digitalization of Russian universities such as the lack of interactive innovative forms of online support of applicants by Russian universities; the lack of digital footprints of the educational process, especially video lessons; depersonalization of digital support of training; non-competitive descriptions of elective courses, the lack of educational case studies as a main technology for the implementation of practice-oriented tasks; the underdevelopment of interaction as a basic principle for providing online support of the educational process. As the prospects of the study, the article makes the case for constructing a model ranking universities according to the level of digital space development.